Accessibility and Effectiveness of Social Security Granted to People Living with HIV and Members of Their Households - Chepurko, G. (Социология: теория, методы, маркетинг, 2015)
The paper presents some results of the research concerning the availability and effectiveness of social protection in Ukraine for working-age people living with HIV (PLHIV) and members of their families.